Penerapan Algoritma Weight Product Sebagai Sistem Pendukung Keputusan Dalam Mengambil Keputusan Penerima Beasiswa Berbasis Website Pada MA Babul Ulum Mariana - M Bronly Mangku Pandita; Firamon Syakti; M Soekarno Putra (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2025)
Accepting a scholarship at Madrasah Aliyah (MA) Babul Ulum Mariana is an important process that requires an effective decision support system. This research aims to implement the Weight Product (WP) Algorithm Method as a website-based decision support system to assist decision making for scholarship recipients. The research methodology includes requirements analysis, system design, implementation of the Product Weight algorithm, and system testing. Scholarship selection criteria are identified and weighted according to their level of importance. Data on prospective scholarship recipients is entered into the system to be processed using the Weight Product Algorithm. This research was conducted to understand the concept of the Weight Product (WP) Algorithm and decision making in the context of scholarship acceptance. Research includes implementing a web-based system by implementing the WP method, system performance testing, and results analysis. It is hoped that the results of this research will show that a website-based decision support system using the Weight Product (WP) Algorithm method can help make decisions on scholarship recipients effectively. This research can be used as a basis for system development at Madrasah Aliyah (MA) Babul Ulum Mariana.